Microcomputer accounting : - Anders, Gregory E. (McGraw-Hill, 2002)
This text-workbook consists of 14 tutorial chapters that provide extensive coverage of accounting topics and offers a balance between reading and hands-on activities. Each chapter features an end-of-chapter application problem. The text and template disks are compatible with Peachtree Complete, Release 8.0.